Determinants of Bank Kerjasama Rakyat Malaysia Berhad profitability / Anis Hafizah Zainal ‘Amini - Zainal ‘Amini, Anis Hafizah (Faculty of Business and Management, 2012)
The research studies on the determinants of Bank Kerjasama Rakyat Malaysia Berhad profitability. This study basically focuses on the relationship of internal variables with bank’s profitability. There are three internal variables which are chosen in this study namely total loan, total deposit and total expenditure. The objective of this study is to determine the relationship between total loans, total deposits and total expenditure towards bank’s profit. The data period cover from April 2007 until December 2010 (45 months), retrieved from bank’s monthly balance sheet and profit loss statements. The Multiple Linear Regression (MLR) Model is used to investigate the relationship between all independent variables with dependent variables. The result of the study obtained only two of the variables is significant which is total loans and total expenditure. As quoted by Sudin Haron (2004), his study finds that internal factors such as liquidity, total expenditures, funds invested Islamic securities, and the percentage of the profit-sharing ratio between the bank and the borrower of funds are highly correlated with the level of total income received by the Islamic banks. His findings where total deposits from customer is not significant with profitability results the same in this research.